Metabolic Power in Team Sports - Part 1: An Update - di Prampero, Pietro Enrico; Osgnach, Cristian (International Journal of Sports Medicine, 2018)
Team sports are characterised by frequent episodes of accelerated/decelerated running. The corresponding energy cost can be estimated on the basis of the biomechanical equivalence between accelerated/decelerated running on flat terrain and constant speed running uphill/downhill. This approach allows one to: (i) estimate the time course of the instantaneous metabolic power requirement of any given player and (ii) infer therefrom the overall energy expenditure of any given time window of a soccer drill or match. In the original approach, walking and running were aggregated and energetically considered as running, even if in team sports several walking periods are interspersed among running bouts. However, since the transition speed between walking and running is known for any given incline of the terrain, we describe here an approach to identify walking episodes, thus utilising the corresponding energy cost which is smaller than in running. In addition, the new algorithm also takes into account the energy expenditure against the air resistance, for both walking and running. The new approach yields overall energy expenditure values, for a whole match,≈14% smaller than the original algorithm; moreover, it shows that the energy expenditure against the air resistance is≈2% of the total.
Keywords: acceleration/deceleration; energy cost; tracking systems; walking/running; air resistance; metabolic power